MODEL KEMITRAAN PEMBIBITAN UNTUK MEGHASILKAN BIBIT KELAPA SAWIT BERKELANJUTAN DI SUMATERA UTARA - Tri Martial; Mhd. Asaad; Aldywaridha Aldywaridha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The long term goal is to build a model of the nursery business partnerships forsustainable palm oil seedlings in order to meet the needs of oil palm seedlings in NorthSumatra. Specific targets to be achieved is to build partnerships in the nursery withnursery growers to produce quality seeds. The method used is to adopt a sustainableapproach in developing oil palm breeding in the Faculty of Agriculture UISU.Sustainable approach a synthesis of elements of ecological sustainability, economicsustainability and social sustainability / culture.Ecological sustainability is to maximize organic inputs to farming, by reducing asmuch as possible inputs inorganic. Attempts were made to provide good medium forseed planting with various organic materials such as compost, green manure andmanure, and the use of botanical pesticides. Nurseries carried out in two phases,namely pre-nursery and nursery. Economic sustainability is the nursery businessmanagement is set such that it becomes a source of income on an ongoing basisthroughout the year. Social sustainability / culture is to involve the community /farmers as seedlings and marketing partners. Partnership with emphasize to increasethe farmers capacity encourage farmers to produce quality seedlings and supportsustainability Keywords: Oil palm seedlings, sustainable, farmers' capacity, partnerships